K27-linked ubiquitination of BRAF by ITCH engages cytokine response to maintain MEK-ERK signaling - Qing Yin (Nature Portfolio, 2019)
BRAF drives MEK/ERK activation to facilitate tumorigenesis. Here, the authors show that in response to pro-inflammatory cytokines, ITCH mediates a non-proteolytic ubiquitination and activation of BRAF, which in turn sustains MEK/ERK signaling to facilitate melanoma cell growth.